2021
DOI: 10.1192/bjo.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor levels in newly diagnosed patients with bipolar disorder, their unaffected first-degree relatives and healthy controls

Abstract: Background Brain-derived neurotrophic factor (BDNF), which facilitates neuroplasticity and synaptogenesis, may be decreased in bipolar disorder, but has not been systematically investigated in people with newly diagnosed bipolar disorder and unaffected first-degree relatives. Aims To compare BDNF levels in patients with newly diagnosed bipolar disorder, their unaffected first-degree relatives and healthy controls. Method The study investigated plasma BDNF levels in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
5
1
1
Order By: Relevance
“…However, some studies also indicated an increased level of BDNF among patients with newly diagnosed BD—up to 22% compared to the control group. It was also noted that the level of BDNF positively correlated with the duration of the disease, which is in contrast to the results of other studies [ 147 ], which showed that BDNF is reduced only in patients with advanced stage of BD, and its levels decline with the duration of the disease [ 148 ]. Lin et al (2016) also did not seem to confirm the reduction in BDNF in manic patients.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…However, some studies also indicated an increased level of BDNF among patients with newly diagnosed BD—up to 22% compared to the control group. It was also noted that the level of BDNF positively correlated with the duration of the disease, which is in contrast to the results of other studies [ 147 ], which showed that BDNF is reduced only in patients with advanced stage of BD, and its levels decline with the duration of the disease [ 148 ]. Lin et al (2016) also did not seem to confirm the reduction in BDNF in manic patients.…”
Section: Resultscontrasting
confidence: 74%
“…These results, however, are not consistent in all cases and there are studies that do not show a decrease in BDNF, or even its increase among patients who developed “long-COVID” [ 160 ]. The decrease in BDNF is also noticeable among patients with BD, although the opposite results can be found in this case as well [ 144 , 145 , 147 ]. Such a picture may correspond to the hypothesis that there is an overall decrease in BDNF during the course and progression of BD, but manic episodes may be triggered by a temporary and rapid increase in BDNF secretion [ 150 ].…”
Section: Resultsmentioning
confidence: 86%
“…In addition, we found a significantly positive correlation between levels of FARSB and BDNF in both patients and controls. A previous study reported decreased peripheral BDNF in BD in the later stage [19]; however, one recent study found that BDNF levels were increased in early-staged BD [35]. The study by Petersen et al [35] suggested that increased BDNF in patients with BD in the early stage of the illness compared to controls may be explained by ( 1) younger age of the study group as well as (2) in-time diagnosis and in-time treatment intervention.…”
Section: Farsb Protein and Bdnfmentioning
confidence: 95%
“…A previous study reported decreased peripheral BDNF in BD in the later stage [19]; however, one recent study found that BDNF levels were increased in early-staged BD [35]. The study by Petersen et al [35] suggested that increased BDNF in patients with BD in the early stage of the illness compared to controls may be explained by ( 1) younger age of the study group as well as (2) in-time diagnosis and in-time treatment intervention. Another meta-analysis comprised of 3798 participants found that BDNF levels increased with illness duration of BD [36].…”
Section: Farsb Protein and Bdnfmentioning
confidence: 95%
“…Speci cally, mood episodes include mania, hypomania, and alternating episodes of depression (Grande et al, 2016). Although no speci c biomarker has been identi ed, individuals with BD present with increased peripheral levels of in ammatory and oxidative stress markers accompanied by altered levels of neurotrophic factors (van den Ameele et al, 2020Ameele et al, , 2017Fernandes et al, 2011;Ghafouri-Fard et al, 2019;Kim et al, 2007;Petersen et al, 2021). Hence, BD is associated with a chronic low-grade in ammatory state, which seems to be coordinated with mood symptoms and cognitive de cits during the cour Bipolar disorder (BD) is a recurrent chronic and disabling disorder characterized by uctuations in mood, energy, and functioning (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%